2020
DOI: 10.1002/asi.24358
|View full text |Cite
|
Sign up to set email alerts
|

“We're being tracked at all times”: Student perspectives of their privacy in relation to learning analytics in higher education

Abstract: Higher education institutions are continuing to develop their capacity for learning analytics (LA), which is a sociotechnical data mining and analytic practice. Institutions rarely inform their students about LA practices and there exist significant privacy concerns. Without a clear student voice in the design of LA, institutions put themselves in an ethical grey area. To help fill this gap in practice and add to the growing literature on students' privacy perspectives, this study reports findings from over 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 52 publications
1
61
0
Order By: Relevance
“…Linked to this are clearly privacy issues, implying consent, the right to control over the use of one's data and the right to withdraw (Fjeld et al, 2020). Yet a recent study by Jones (2020) found students knew little of how LA were being used in their institution or remembered consenting to allowing their data to be used. These would all be recognised as issues by most AI projects.…”
Section: Ai and Robotics In Research: Fiction 5 "The Research Management Suite Tm"mentioning
confidence: 99%
“…Linked to this are clearly privacy issues, implying consent, the right to control over the use of one's data and the right to withdraw (Fjeld et al, 2020). Yet a recent study by Jones (2020) found students knew little of how LA were being used in their institution or remembered consenting to allowing their data to be used. These would all be recognised as issues by most AI projects.…”
Section: Ai and Robotics In Research: Fiction 5 "The Research Management Suite Tm"mentioning
confidence: 99%
“…Scholars have identified student privacy as a critical condition necessary to enable and protect the pursuit of ideas and development speech [20]. Students may alter their natural behaviors when digitally surveilled by reducing their engagement in contentious but important debates around politics, religion, and social values.…”
Section: Privacy and Ethics Issuesmentioning
confidence: 99%
“…Research on user perspectives of learning analytics, much like the ethics of the sociotechnical practice, remains focused on students. For example, some research raises questions about privacy rights and system design expectations ( [20], [26], see [36]- [38]). But what of faculty?…”
Section: Faculty Perspectives and Problemsmentioning
confidence: 99%
“…In their study, Perry et al (2018) report that 58% of academic library survey respondents declared that they do not inform patrons that data associated with their behaviours are collected and analyzed. In a recent study involving 100 undergraduate participants from eight higher education institutes in the United States, Jones et al (2020) learned that none of the students remember consenting to data collection and use. These results contrast with findings from unrelated research that more than 90% of full-time instructors (n = 502) surveyed from colleges and universities in the United States agreed that they felt obligated to protect student privacy (VanScoy et al, 2020).…”
Section: Requiring Informed Consent From Participantsmentioning
confidence: 99%
“…Opponents of learning analytics may argue that the collection and analysis of student and patron data transgresses research ethics protocols, and that learning analytics should be held to the same standards in academia as any other behavioural study. Multiple researchers recognize a discrepancy between learning analytics practices on the one hand, and research ethics and review board requirements on the other (Drachsler & Greller, 2016;Jones, 2019;Jones et al, 2020). Pardo and Siemens (2014) in particular bring to light concerns about intersections of the two: "Although educational institutions typically have human research ethics committees or institutional review boards that already process the requests to carry research initiatives involving the collection of personal data, learning analytics poses some new boundary conditions" (p. 442).…”
Section: )mentioning
confidence: 99%